Intervenção online sobre habilidades sociais para mães de crianças com TEA - Silva, Letícia Thays Bessa (2023)
The Autism Spectrum Disorder (ASD) impacts both diagnosed children and their families significantly. Domains frequently affected include communication, social interaction, and restrictive and repetitive patterns of interests or activities. These patterns manifest before school age and may result in deficits in various areas of development. This study suggests that an online intervention aimed at teaching social skills may bring significant benefits to mothers of children with ASD. This can result in improvements in knowledge about ASD, increased confidence in their parenting skills, and substantial improvement in family interactions. The proposed online approach has the advantage of being accessible, overcoming geographical and logistical barriers. This is particularly relevant in contexts where resources for in-person intervention may be limited, making research an effective way to explore accessible and effective options. This study seeks to fill a gap in research and provide empirical evidence on a specific online intervention for mothers of children with ASD. The research was designed as an intervention study. By focusing on mothers and their parenting skills, this study acknowledges the importance of a supportive and understanding environment for mothers of children with ASD. The overall objective is to analyze an online intervention on social skills for mothers of children with ASD. The specific objectives of this study are: to describe common needs of mothers of children with ASD; to analyze the frequency of co-occurrence of social skills classes and themes in intervention sessions; to analyze the social validity of the intervention; and to analyze the secondary effects of the intervention on children's Social Skills repertoire. The participant sample was non-probabilistic, convenience type, with the participation of six mothers. The instruments used were: Identification Form; Brazil Economic Classification Criterion; Social Skills, Behavior Problems, and Academic Competence Inventory for Children; Social Validation Questionnaire; and Follow-up Questionnaire with mothers. Data collection involved conducting six individual training sessions with each mother, during which the researcher provided guidance on personalized strategies for each child. Additionally, it included sending support materials and continuous feedback through an instant messaging application. Records were made from the application of the instruments: researcher's field diaries, recording of all meetings held, materials, and videos shared by the mothers. For analysis, there was tabulation of specific results per instrument and descriptive data, organized thematically. ATLAS TI software was used for data analysis. The results of the Social Skills, Behavior Problems, and Academic Competence Inventory for Children indicate that there were changes in the classification of children's social skills based on the intervention conducted with the mothers. Thematic analysis occurred, which allowed dialogue with the theoretical framework in four themes: mothers' need for guidance on how to mediate interaction with peers; improving the family-school relationship; difficulty controlling children's screen time; and difficulty reporting what happened at school. The results of the ATLAS TI software indicate that "communication" was the most cited skill and "affection/cooperation" the least cited. It was evident that there is less co-occurrence between "responsibility" and "making and maintaining friendships" and "responsibility" and "affection/cooperation", with greater co-occurrence between "communication" and "social poise", as well as between "communication" and "interpersonal problem solving". Thus, the data obtained meet the proposed objectives, manage to indicate positive aspects of the proposed short-term online intervention, especially from the mothers' discourse and the results of social validation, and suggest that future research be conducted.